The ability of compound sentences translation of the English Department Students of UNP Kediri / Pamadya Vitasmoro and Agung Wicaksono - Vitasmoro, Pamadya; Wicaksono, Agung (2021)
This study builds on to find out the ability of compound sentences' translation of the English Department student of UNP PGRI Kediri. The research design is descriptive qualitative. The subject of the study was the student of the seventh semester who has taken translation subject, They were 28 students. The researcher gives the predicate for each translation, and for each predicate, the researcher gives the criteria as follows: 1. Almost perfect, 2. Good, 3.Satisfactory, 4.Poor, 5. Very Poor. The result of the research the ability to translate compound sentence with the conjunction "and" are 10% is almost perfect, 79% is good, 4% is enough, and 7% is poor. Compound sentence with the conjunction "but" are 50% is almost perfect 25% is good, 25% is poor. Compound sentences with the conjunction "for" are 14% are almost perfect, 14% is good 65% is enough, 7% is very poor. Compound sentence with the conjunction "so" is 54% is almost perfect, 36% is good and 10% enough. A compound sentence with the conjunction "or" is 28% is almost perfect 54% is good 4% is enough, and 10% is poor and 4% is very poor. So, it can be concluded that the ability of compound sentences translation is good.